2022
DOI: 10.1096/fj.202101507rr
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide CRISPR activation screen reveals Hexokinase 1 as a critical factor in promoting resistance to multi‐kinase inhibitors in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is often diagnosed at an advanced stage and is, therefore, treated with systemic drugs, such as tyrosine‐kinase inhibitors (TKIs). These drugs, however, offer only modest survival benefits due to the rapid development of drug resistance. To identify genes implicated in TKI resistance, a cluster of regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 activation screen was performed in hepatoma cells treated with regorafenib, a TKI used as second‐lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Tyrosine kinase inhibitors are considered to be the first-line therapy for patients with advanced or metastatic HCC. Of note, transcriptome analysis [ 14 ] demonstrated that TRIM15 was abnormally upregulated in regorafenib-resistant HCC cell lines (Fig. 1a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine kinase inhibitors are considered to be the first-line therapy for patients with advanced or metastatic HCC. Of note, transcriptome analysis [ 14 ] demonstrated that TRIM15 was abnormally upregulated in regorafenib-resistant HCC cell lines (Fig. 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…3d . In addition, we analyzed the RNA-seq data comparing the difference between regorafenib-resistant and -sensitive HCC cells reported by Sofer S et al [ 14 ]. (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hexokinase (HK), the first glycolytic pathway enzyme, can be upregulated by hypoxia, which is associated with HCC resistance to regorafenib. 277 Mechanistically, hypoxia stabilizes HIF-1α by ubiquitin-specific peptidase (USP29) and then transcriptionally activates HK. 278 Pyruvate kinase M2 (PKM2), another rate-limiting enzyme of glycolysis, is overexpressed in TKI treatment, accompanied by high levels of lactate production.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%
“…Genome-scale perturbation with CRISPRa can be achieved by synthesizing a genome-wide sgRNA library, bypassing the need to generate a genome-wide ORF library. CRISPR-based GOF approaches have been used for genome-wide genetic screens in mammalian cells ( Konermann et al, 2015 ; Rodríguez et al, 2022 ; Zhu et al, 2022 ; Sofer et al, 2022 ; Zhang et al, 2022 ), but the feasibility has not yet been tested in Drosophila cells.…”
Section: Introductionmentioning
confidence: 99%